Perceived gains from changes in book allowance regime: case of a South African public university - Dominique Emmanuel Uwizeyimana; Victor H. Mlambo (Cogent Education, 2025)
This study evaluated the perceived impact of the revised National Student Financial Aid Scheme (NSFAS) book allowance disbursement system on student academic performance at a South African public university. The study compared academic performance before and after the implementation of the new system, looking at flexibility and autonomy, cost management and availability of study materials as attributes of interest. Data were collected from a purposive sample of 91 students under the School of Public Management, Governance and Public Policy who had experienced both the new and old systems as part of the academic journey. Online and traditional survey methods were used, and the data were analysed using IBM SPSS. Tests included descriptive statistics, t-tests to test for academic performance perceptions differences in the old versus new system and Fisher’s exact tests to assess how academic performance was associated with identified attributes of the new system. The findings show that under the new system, the advantages of autonomy, flexibility and cost management in book allowance use increased. The prescribed textbook availability advantage, however, was declined. Regardless, there was an overall perception of (1) academic improvement and (2) neutrality in academic performance even when the actual prescribed textbook availability declined. The study recommends strengthening students’ capacities to autonomously manage their book allowance usages while at the same time facilitating the availability of OER and students’ abilities to evaluate OER quality. This two-pronged approach will narrow the gap between costs and expenditure, enabling students’ allowance to stretch a bit longer while supporting stable or improved academic performance.